Multi-agent based distributed control architecture for microgrid energy management and optimization - Basir Khan M.R.; Jidin R.; Pasupuleti J. (Elsevier Ltd, 2023)
Closed loop control systems; Computer architecture; Decentralized control; Distributed parameter control systems; Distributed power generation; Electric power system interconnection; Energy management; Energy resources; Fault tolerance; Game theory; Multi agent systems; Renewable energy resources; Decentralized control architecture; Distributed control architectures; Distributed Energy Resources; Distributed generation system; Micro grid; Multi agent; Non-cooperative game theory; Renewable energy systems; Energy management systems